Real time laser interference microscopy for bar‐spread polystyrene/poly(methyl methacrylate) blends. Issue 15 (7th June 2014) - Haq, Ehtsham Ul; Toolan, Daniel T. W.; Emerson, Jillian A.; Epps, Thomas H.; Howse, Jonathan R.; Dunbar, Alan D. F.; Ebbens, Stephen J.
ABSTRACT We demonstrate that real‐time laser interference microscopy can be used to directly observe the dynamics of film formation and phase separation processes for a bar‐spread polystyrene/poly(methyl methacrylate) blend. The ability to dynamically image laser interference patterns allows compete drying curves and polymer content to be determined throughout the film formation process. The polymer content at which phase separation structure first is observed in the interference micrograph sequence is in good agreement with calculated spinodal curves. Morphology evolution proceeds from phase separation onward via coarsening and coalescence to arrive at the final domain structure. In comparison, spin coating the same polymer blend results in structure evolution being quenched further from equilibrium due to the faster drying rate. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2014, 52, 985–992